Optimasi Formula Tablet Effervescent Ekstrak Kelopak Bunga Rosela Dengan Kombinasi Avicel PH 101 Dan Gelatin (Aplikasi Metode Simplex Lattice Design) - Widodo Priyanto (Fakultas Farmasi Universitas Setia Budi, 2011)
Avicel PH 101 is an excipient in tablet making that can be used as diluent, binder, lubricant, and disintegrator. Avicel is not economically an advantage so that it needs to be combined with cheaper materials. Combination of Avicel PH 101 with gelatin starch is able to accelerate the disintegration time of the effervescent tablet. Rosela (Hibiscus sabdariffa L) rose is a traditional medicine that is used as antiinflammation. The study was to find out the optimum proportion of Avicel PH 101 and gelatin mixture in effervescent tablet making of rosella rose extract by simplex lattice design method. The extract of rosella rose was obtained by maceration of rosella rose powder with ethanol 70%. The obtained extract was evaporated until a thick extract was obtained. Effervescent tablet formulation was based on SLD method with excipients of Avicel PH 101 (A) and gelatin (B) i.e. F1 (100% A), F2 ( 50% A : 50% B), F3 (100% B). The effervescent tablets of rosella rose extract were made by a direct compression methods. Physical characteristic test of the tablets included weight uniformity test, hardness test, friability test, disoluble time test and taste perception test. The equation was used to make effervescent tablets with total respond of the most optimum granules physical properties. The data of the physical properties of granules from optimum formula as calculation result based on SLD equation with the experiment result was analyzed using T-test. Effervescent tablets from optimum formula were physically tested including weight uniformity, hardness, friability and taste perception test. The result of the experiment indicated that the mixture of 90% Avicel PH 101 – 10% gelatin produced an optimum result in granules physical properties and the obtained effervescent tablets of rosella rose extract fulfilled tablet physical property test.